2014
DOI: 10.1103/physrevlett.112.095302
|View full text |Cite
|
Sign up to set email alerts
|

Interaction-Tuned Dynamical Transitions in a Rashba Spin-Orbit-Coupled Fermi Gas

Abstract: We consider the time evolution of the magnetization in a Rashba spin-orbit-coupled Fermi gas, starting from a fully-polarized initial state. We model the dynamics using a Boltzmann equation, which we solve in the Hartree-Fock approximation. The resulting non-linear system of equations gives rise to three distinct dynamical regimes with qualitatively different asymptotic behaviors of the magnetization at long times. The distinct regimes and the transitions between them are controlled by the interaction strength… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…This might establish a link to relevant condensed matter systems where such demagnetization mechanisms are well-studied [59][60][61]. Such dynamics have recently been examined in the case of thermal Fermi gases in the collisionless regime [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…This might establish a link to relevant condensed matter systems where such demagnetization mechanisms are well-studied [59][60][61]. Such dynamics have recently been examined in the case of thermal Fermi gases in the collisionless regime [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…For the Bose system, the spin dynamics of the Bose-Einstein condensation has attracted much attention. [1][2][3][4][5][6][7][8] For the Fermi cold atoms, the systems without [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and with [26][27][28][29][30][31][32] spin-orbit coupling (SOC) are extensively investigated. In the absence of the SOC, many interesting phenomena, such as the Leggett-Rice effect in unitary gas [17][18][19][20][21] and anomalous spin segregation in extremely weak scattering limit, [22][23][24][25] have enriched the understanding of the spin dynamics of Fermions.…”
Section: Introductionmentioning
confidence: 99%
“…With the synthetic SOC experimentally realized by laser control technique in cold atoms, 7,8,26,27 the spin relaxation for the Fermi cold atoms with SOC has been studied both experimentally [26][27][28] and theoretically. [29][30][31][32] This is partly motivated by the wellcontrolled laser technique, which provides more freedom for the cold atoms than the conventional solids. On one hand, rich regimes can be realized by tuning the SOC strength; on the other hand, not only the interatom interaction can be tuned by the Feshbach resonance, 33 but also the atom-disorder interaction can be introduced and controlled by the speckle laser technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the topological phase can be realized in a narrow parameter regime even at finite temperature though the Zeeman field is (much) larger than the pairing strength [32,33], so the induced p-wave pairing provides a new mechanism to go beyond the Chandrasekhar-Clogston limit [43,44]. The recent interests in this system also include the topological inhomogeneous superfluids [37][38][39], the quench dynamics of the topological superfluids [40,41] and the topological superradiant state [42]. Thus the exploring of these exotic phases in this model is still an important topic in modern research.…”
Section: Resultsmentioning
confidence: 88%